Proposing a Core Outcome Set for Physical Activity and Exercise Interventions in People With Rare Neurological Conditions - Ramdharry, Gita; Buscemi, Valentina; Boaz, Annette; Dawes, Helen; Jaki, Thomas; Jones, Fiona; Marsden, Jonathan; Paul, Lorna; Playle, Rebecca; Randell, Elizabeth; Robling, Michael; Rochester, Lynn; et al. (Frontiers in Rehabilitation Sciences, 2021)
Rare neurological conditions (RNCs) encompass a variety of diseases that differ in progression and symptoms but typically include muscle weakness, sensory and balance impairment and difficulty with coordinating voluntary movement. The aim of this study was to agree a core outcome measurement set for physical activity and exercise interventions in people living with RNCs. We followed the practice guidelines of the COSMIN and COMET initiatives to develop core outcome sets. Broad ranging discussions in a series of workshops led to the consensus that (1) physical well-being; (2) psychological well-being and (3) participation in day-to-day activities should be measured in intervention evaluations. Recommendations were further informed by a scoping review of physical activity and exercise interventions for people living with RNCs. Nearly 200 outcome measures were identified specific focus on activities or functions (e.g. on lower limb function, ability to perform daily tasks) but limited consideration of participation based outcomes. The Oxford Participation and Activities Questionnaire, a short, 23-item, patient-reported outcome measure broadly assessing constructs across Routine Activities (14 items), Emotional Well-Being (5 items) and Social Engagement (4 items) and the Sources of Self-Efficacy for Physical Activity were proposed as being particularly relevant in physical activity interventions. Validation work across rare neurological conditions is now required to inform application of this core outcome set in future clinical trials to inform syntheses of results and meta-analyses.